LIVING WELL. Issue 38 (30th September 2014) - Cahn, Steven M.; Vitrano, Christine
<x content-type="archive" xml:space="preserve">Abstract</x> What is living well? We describe two contrasting lives and ask whether one is better lived than the other. Many philosophers, among them Susan Wolf, Richard Kraut and Stephen Darwall would say so. We criticize their position, which views certain activities as intrinsically more worthy than others. Instead, we conclude that persons are living well if they act morally and find long-term satisfaction, regardless of the pursuits they choose.